PERILAKU INFORMASI CONTENT CREATOR JEJARING SOSIAL BERBASIS VIDEO - Aypa Berhama Zega, Derin; Safii, Moh.; Roekhan (BACA: Jurnal Dokumentasi dan Informasi, 2022)
Information search is carried out by all groups to support their daily work. This is also done by content creators as content creators so that the content shared is accurate and useful. This study aims to describe the information behavior of content creators using David Ellis' information behavior model. This research is a type of qualitative research. Data collection techniques with interviews and documentation studies. Sampling in the study was selected through a purposive sampling technique. Through this technique, two people were chosen to act as content writers and editors as informants in this study because they were directly involved in developing story ideas and writing video scripts for the "How come?" Youtube channel. Data analysis through data reduction, coding, data presentation, and drawing conclusions. The results of the study found that in the early stages, content creators identified their information needs through the main literature; chaining, understanding information, enriching information sources; browsing, tracing information sources both digital and print media; differentiate, choose sources of information according to the preferences of content creators; monitoring, monitoring the flow of development of information sources; extracting, identifying and recording information points; verify, re-check the information that has been collected; ending, do the packaging and share the videos that have been made. The conclusion of the study shows that content creator search behavior is an active information search behavior because they know the need for information and try to fulfill it by finding and selecting sources of information. The results of the analysis show that the main factors that drive information needs into information seeking behavior are due to job demands and their desire to share informative and educative content with audiences. In addition, information search is also carried out to increase their knowledge and insight.